(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
The problem of extrahepatic bile duct (EHD) lesions in complicated cholelithiasis has remained one of the central issues in abdominal surgery over the past decades. The development of minimally invasive technologies has radically changed the tactics of surgical treatment of complicated forms of cholelithiasis (CD) (1,2,3,4).